2020
DOI: 10.1155/2020/8814588
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Hybrid RF/FSO Cooperative Systems Based on Quasicyclic LDPC Codes and Space-Coupled LDPC Codes

Abstract: Free space optical (FSO) communication systems provide wireless line of sight connectivity in the unlicensed spectrum, and wireless optical communication achieves higher data rates compared to their radio frequency (RF) counterparts. FSO systems are particularly attractive for last mile access problem by bridging fiber optic backbone connectivity to RF access networks. To cope with this practical deployment scenario, there has been increasing attention to the so-called dual-hop (RF/FSO) systems where RF transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…A gamma distribution was used to describe the FSO connection, and the White Gaussian noise (AWGN) model was used to simulate the frequency correlation. The results showed that the performance of the cooperating RF/FSO DF system based on QC-LDPC and SC-LDPC codes was better than that of RF/FSO systems without codes [49].…”
Section: Journal Of Robotics and Control (Jrc)mentioning
confidence: 98%
“…A gamma distribution was used to describe the FSO connection, and the White Gaussian noise (AWGN) model was used to simulate the frequency correlation. The results showed that the performance of the cooperating RF/FSO DF system based on QC-LDPC and SC-LDPC codes was better than that of RF/FSO systems without codes [49].…”
Section: Journal Of Robotics and Control (Jrc)mentioning
confidence: 98%
“…Li et al [124] analyzed the outage probability, average BER, and average transmission rate of a dual-hop link between deep space and terrestrial in a weather-dependent satellite-terrestrial network with a rate adaptation hybrid RF/FSO link. Gueye et al, in [125], investigated the performance of cooperative transmission systems in FSO communication. Their study focused on dual-hop systems, combining RF and FSO transmission.…”
Section: Physical Layer Designmentioning
confidence: 99%